For Ever and Ever the Perfect Wedding Picture: Converging Religious and Secular Norms and Values in Wedding Photography - Mäder, Marie-Therese (Religions, 2024)
The paper examines how stylistic norms of wedding photography express, affirm, adapt, and reshape religious and secular values by combining ethical considerations with qualitative ethnographic observations. The first part offers a critique of the distinction between civil secular and religious weddings in current scholarship. In the second part, the relation between norms and values in an ethics of wedding photos is elaborated. The discussion is illustrated with examples from a study with 27 married couples and their wedding photos. The study reveals two key aspects: In the production of wedding photos, the triangular relation between the couple, their guests, and the location, the so-called locationship, is staged through the lens of the camera. In this triangle, the blending of religious and secular norms and values could be observed. Another significant aspect is how norms and values originating from wedding photography of religious ceremonies continue to impact secular norms and values. It is particularly noteworthy that religion serves as an aesthetic matrix in wedding photography, contributing to a “visual enchantment”, irrespective of whether the ceremony is religious or secular in nature.